Role of NPR2 mutation in idiopathic short stature: Identification of two novel mutations. Issue 3 (20th January 2020) - Hwang, Il Tae; Mizuno, Yusuke; Amano, Naoko; Lee, Hye Jin; Shim, Young Suk; Nam, Hyo‐Kyoung; Rhie, Young‐Jun; Yang, Seung; Lee, Kee‐Hyoung; Hasegawa, Tomonobu; Kang, Min Jae
Abstract: Background: C‐type natriuretic peptide (CNP, NPPC ) and its receptor, natriuretic peptide receptor‐B (NPR‐B, NPR2 ), are critical for endochondral ossification. A monoallelic NPR2 mutation has been suggested to mildly impair long bone growth. This study was performed to identify the NPR2 mutations in Korean patients with idiopathic short stature (ISS). Methods: One hundred and sixteen subjects with nonsyndromic ISS were enrolled in this study, and the NPPC and NPR2 were sequenced. In silico prediction and in vitro functional analysis, using a cell‐based assay, were performed to confirm their protein derangement. Results: Mean age at diagnosis of ISS was 8.0 years, and the height z ‐score was −2.65. Three pathogenic variants (R921Q, R495C, and Y598N) and one benign variant (R787W) of the NPR2 were identified, while no novel sequence variant of the NPPC was found in all subjects. Two novel pathogenic mutants (R495C and Y598N) were predicted as highly pathogenic by several computational methods. In vitro study involving stimulation with CNP, R495C‐, and Y598N‐transfected cells showed decreased cGMP production compared to wild type‐transfected cells. Conclusion: Heterozygous NPR2 mutations were found in 2.6% of ISS Korean subjects. This prevalence and the dominant‐negative effect of mutant NPR‐B on growth signals imply that it is one of genetic causes of ISS. Abstract : This is a mutation study and functional analysis of the NPR2 and NPPC genes in Korean patients with idiopathic short stature (ISS) to identify heterozygous mutations in the CNP and NPR‐B system in relation to short stature. We identified mutations in ISS patients that yielded two novel NPR‐B variants (R495C, Y598N) not found in the dbSNP nor Korean genome databases. These variants were suggested to be highly pathogenic by in silico prediction models and their dominant‐negative effects were confirmed by our functional analysis.